2023
DOI: 10.1101/2023.09.25.559415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancers associated with unstable RNAs are rare in plants

Bayley R. Mcdonald,
Colette Picard,
Ian M. Brabb
et al.

Abstract: Unstable transcripts have emerged as markers of active enhancers in vertebrates and shown to be involved in many cellular processes and medical disorders. However, their prevalence and role in plants is largely unexplored. Here, we comprehensively captured all actively initiating (“nascent”) transcripts across diverse crops and other plants using capped small (cs)RNA-seq. We discovered that unstable transcripts are rare, unlike in vertebrates, and often originate from promoters. Additionally, many “distal” ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
2
1
0
Order By: Relevance
“…Despite these similarities, enhancers in plants and animals differ in their histone modifications ( Lu et al 2019 ; Yan et al 2019 ; Silver et al 2023 ). The absence in plants of the canonical histone modifications that mark active enhancers in animals is consistent with the absence in plants of the bi-directional, short-lived enhancer RNAs found in animals ( Erhard et al 2015 ; Hetzel et al 2016 ; Thieffry et al 2020 ; Mcdonald et al 2023 ; Silver et al 2023 ). Thus, plants appear to use different mechanisms than animals for maintaining enhancer activity.…”
Section: Introductionsupporting
confidence: 75%
“…Despite these similarities, enhancers in plants and animals differ in their histone modifications ( Lu et al 2019 ; Yan et al 2019 ; Silver et al 2023 ). The absence in plants of the canonical histone modifications that mark active enhancers in animals is consistent with the absence in plants of the bi-directional, short-lived enhancer RNAs found in animals ( Erhard et al 2015 ; Hetzel et al 2016 ; Thieffry et al 2020 ; Mcdonald et al 2023 ; Silver et al 2023 ). Thus, plants appear to use different mechanisms than animals for maintaining enhancer activity.…”
Section: Introductionsupporting
confidence: 75%
“…Despite these similarities, enhancers in plants and animals differ in their histone modifications (Lu et al, 2019; Yan et al, 2019; Silver et al, 2023). The absence in plants of the canonical histone modifications that mark active enhancers in animals is consistent with the absence in plants of the bi-directional, short-lived enhancer RNAs found in animals (Erhard et al, 2015; Hetzel et al, 2016; Thieffry et al, 2020; Mcdonald et al, 2023; Silver et al, 2023). Thus, plants appear to use different mechanisms than animals for maintaining enhancer activity.…”
Section: Introductionsupporting
confidence: 75%
“…The study of cis-regulatory regions in plants have revealed similar molecular signatures 18 , although H3K4me1 is found in gene bodies rather than distal enhancers 9,19,20 , and the presence of enhancer RNAs is disputed 21 . The catalog of distal elements in maize has been greatly improved by recent efforts to resolve cell-type specific accessible regions with single-cell ATAC-seq experiments 9,19,22 .…”
Section: Introductionmentioning
confidence: 99%